Correntes de blocos em redes virtualizadas: protocolos de consenso e fatiamento seguro da rede - Rebello, Gabriel Antonio Fontes (2019)
[EN] Blockchains are a disruptive technology that will revolutionize our way of living, working and negotiating. Like the Internet today allows transfering files, this new technology will build an Internet of Value, in which it is possible to transfer unique resources such as money, stock, intellectual property, votes, etc. without the need for intermediate entities. One of the main challenges of blockchain-based systems, however, is to choose the consensus protocol to determine the way in which collective decisions are made in each use case. The first part of this work discusses the consensus concepts and models for different types of blockchains. We present several consensus protocols and clarify their features, advantages, disadvantages and main goals. Then, in a second part, we propose to use blockchains to secure the network-slicing-based Internet. Network slicing aims to offer agile and on-demand end-to-end services for each type of application. The main contributions of this second part are: i) the proposal and development of a blockchain-based architecture to provide auditability to network slicing orchestration operations; and ii) a proposal for the categorization of blockchains that address the diverse scenario of applications in future networks. A prototype of the proposed architecture was built using the Hyperledger Fabric platform. In the prototype, each network slice operates in an isolated channel and each blockchain is implemented through a smart contract. The results show that it is possible to provide security to network slice managements, but the consensus latency and transaction throughput might still pose a challenge.